Research on joint vehicle routing optimization considering multiple distribution centers - Di Liu; Mengchi Li; Yushun Lei; Pei Yu; Botang Li; Songyuan Tang (PLoS ONE, 2026)
In order to address the problem of efficiently distributing to multiple demand points within the city and multiple distribution centers on the urban fringes, this paper considers decision-making issues such as the selection of distribution centers and the planning of delivery routes. With the objective of minimizing the total transportation time, an integer programming model for the urban vehicle delivery network is constructed. Moreover, a class of column generation algorithms is designed for the characteristics of the problem. CPLEX is used to compare and analyze the solutions of several examples. The results verify the feasibility of the proposed column generation algorithm, and the practicality of the planning model is demonstrated through the analysis of examples generated from actual data.